The Substitution of Physical Education with Sekolah Alam Student Scout Learning Activities as the Means of Strengthening Education based Character Building in Natural Elementary School Ar-Ridho Semarang (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The current research attempts to study SASS standing for Natural Elementary School Student Scout learning activities covering the roles of SASS as the substituent of physical education, the reason underlying physical and sports education omission, SASS peculiarity in strengthening character building, character value taught in SASS, the participation of SASS in strengthening character building. It also aims at looking into the background of academic of the teachers involved in SASS, general issues in SASS such as planning, execution, and evaluation. It is qualitative research with case study research design; data analysis is conducted by using Nvivo 11 software. It is found that physical and sports education is not fully omitted; it is the part of SASS as a school under Jaringan Sekolah Alam Nusantara (a Nature School association in Indonesia). Natural Elementary School Ar-Ridho is mandated to hold SASS because it is the peculiar subject of a Nature School. SASS is the means to train students organizational skill as well as the means to build their character. There are five values of character taught in SASS, namely religiousness, nationalism, self-reliance, cooperation, integrity. Daily activity sheet handed out to the students is the concrete procedure of building students’ character. All the teachers involved in SASS coming from multidisciplinary backgrounds have obtained survival training programs. Generally, SASS is mostly similar to Physical education in term of planning, execution, and evaluation; the differences are in terms of the lesson plan, and mentoring session at the end of SASS class.